1997
DOI: 10.1590/s0036-46651997000500006
|View full text |Cite
|
Sign up to set email alerts
|

Synanthropic rodent reservoirs of Trypanosoma (Schizotrypanum) cruzi in the valley of Caracas, Venezuela

Abstract: Direct blood examination and xenodiagnosis of 47 synanthropic rodents (Rattus rattus, R. norvegicus, Mus musculus) captured in the valley of Caracas, Venezuela, revealed trypanosomal infections in 12 R. rattus, 10 with T. lewisi and 2 with T. cruzi. Of the latter the course of parasitemia, the pleomorphism of the bloodstream trypomastigotes, tissue in naturally and experimentally infected rats and mice, host mortality, morphology of fecal parasites in Rhodnius prolixus used for xenodiagnosis, and infectivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 5 publications
3
19
0
2
Order By: Relevance
“…Other studies have recorded values of 4.6% in New Zealand (Laird 1951), 8.9% in Nigeria (Ugbomoiko 1997), 11.4% in Hawaii (Kartman 1954), 13.2% in both the USA (Eyles 1952) and Egypt (Abdel-Aal & Abou-Eisha 1997), 20% in Italy (De Carnieri & Castellino 1964) and 21.3% in Venezuela (Herrera & Urdaneta-Morales 1997). Unlike in the studies of Franjola et al (1995) and Ugbomoiko (1997) there was a significant difference (p < 0.05) between the infection rates in males (24.9%) and females (16%).…”
Section: Discussionmentioning
confidence: 93%
“…Other studies have recorded values of 4.6% in New Zealand (Laird 1951), 8.9% in Nigeria (Ugbomoiko 1997), 11.4% in Hawaii (Kartman 1954), 13.2% in both the USA (Eyles 1952) and Egypt (Abdel-Aal & Abou-Eisha 1997), 20% in Italy (De Carnieri & Castellino 1964) and 21.3% in Venezuela (Herrera & Urdaneta-Morales 1997). Unlike in the studies of Franjola et al (1995) and Ugbomoiko (1997) there was a significant difference (p < 0.05) between the infection rates in males (24.9%) and females (16%).…”
Section: Discussionmentioning
confidence: 93%
“…In our study, 6 out of 36 females instilled into the vagina became infected, as did 2 out of 14 males instilled into the penis, showing that the mucosa of these organs can be penetrated by the blood form of the parasite, although some workers have found that blood trypomastigotes were less capable of infecting tissues (references in Zeledón et al 1977). Our study appears to show that genital instillation and scrotal inoculation are no less effective than the ip injection employed for isolation of the strains used (Torrealba 1970, Herrera & Urdaneta-Morales 1997.…”
Section: Discussionmentioning
confidence: 66%
“…Three strains of T. cruzi were employed: CO22, isolated from a naturally infected rat, Rattus rattus (Herrera & Urdaneta-Morales 1997); CO57 from a naturally infected opossum, Didelphis marsupialis and human EP (Torrealba 1970). The first two strains were from animals captured in urban areas of Caracas, Venezuela.…”
Section: Methodsmentioning
confidence: 99%
“…Naturally occurring T. cruzi infection of sylvatic Rattus rattus and Rattus novergicus (Rodentia: Muridae) have been described (Herrera & Urdaneta-Morales 1997). Some T. cruzi-infected wild rats showed parasitemia and numerous nests of amastigotes in striated skeletal and cardiac muscle, and in smooth muscle of the digestive tract.…”
Section: Rodentiamentioning
confidence: 99%